Fenomena Kemunculan Sekolah "Elit" Islam di Indonesia (Analisis Aspek Manfaat dan Mudhorot) - Wasilah Wasilah; Muslimah Muslimah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
The emergence of excellent elite schools is expected to answer various problems that are being faced internally by Muslims themselves, namely concerns about the low quality of Islamic education and at the same time provide solutions to the challenges faced by science and technology. Educational policy is formulated by basing itself on a foundation of more scientific and empirical thinking. The study in this study is literature research. Factors that develop the existence of elite schools and madrasas. First, the awareness to design a superior education system. Second, the deterioration of educational processes and outcomes in public schools. Third, skepticism about the process and results of education in pesantren and madrasahs. Fourth, improve economic capabilities. Fifth, government support in private education autonomy and government programs in an effort to "internationalize" all levels of education in Indonesia.